Emotional and rational customer engagement: exploring the development route and the motivation. (27th September 2019) - Chen, Xiao; Dahlgaard-Park, Su Mi; Wen, Decheng
Abstract : Customer engagement is one of the hottest topics in the customer management area. Most of the customer engagement research focus on the customer with strong psychological connection with the focal object, however, the customer who is driven by external benefits, such as discounts and sense of being needed, also contribute significant engagement value to the firm. This paper proposes the constructs of rational customer engagement which is based on external benefits and emotional customer engagement which is based on attachment. The paper distinguishes the two customer engagement orientations from the aspects of development routes and motivations through literature analysis and empirical research. Management implication are also presented in the end. This paper makes contributions to broadening the current customer engagement theory and providing a broader view to understanding customer engagement.